BUILDING THE ENVIRONMENTAL CARE CHARACTER THROUGH MUTUAL COOPERATION ACTIVITIES AT SDN UNYUR - Siti Handayani; Ujang Jamaludin; Suparno (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The background of this research was the importance of the environmental care character built from an early age starting in elementary school, and instilled in various ways; one of which was through mutual cooperation activities. The purpose of this study included two things: first, to determine the mplementation of building the environmental care character through mutual cooperation activities at SDN Unyur and second, to determine strategies to foster the environmental care character through mutual cooperation activities at SDN Unyur. This research was descriptive qualitative research. This research was conducted at SDN Unyur, Serang, Banten. The results showed that the implementation of building environmental care character through mutual cooperation at SDN Unyur included environmental care activities in the classroom, environmental care activities outside the classroom, and annual environmental care activities. The strategy for fostering the environmental care character through mutual cooperation activities at SDN Unyur was instilled by making teachers as role models, giving sanctions and appreciation to students, and providing facilities and infrastructure supporting the manifestation of the environment care character.